On the right to difference and the obligation for tolerance - Chochova, Maria (Law Journal of New Bulgarian University, 2022)
The exhibition analyzes values and legal categories such as tolerance, dignity, as well as the right to non-discrimination through the prism of international law, national law and the practice of the courts. Tolerance is consider as an obligation and differences as characteristics of the individuality of each human being, representing a defensible right.